Pengaruh Garam (NaCl) terhadap Pengendalian Infeksi Argulus sp. pada Ikan Mas (Cyprinus carpio) The Influence of Salt (NaCl) against Argulus sp. Infection Control on Goldfish (Cyprinus carpio) - Anasthazya Christy Hanna Sinaga; Syammaun Usman; Nurmatias Nurmatias (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
The development of goldfish cultivation has a good prospect due to theincreasing market demand. But the attack Argulus sp. on hatchery goldfish is a seriousproblem that can cause a loss of the farmers that is decreased production of fish, as wellas the low value. This research aims to know the extent to which the effectiveness saltagainst Argulus sp. infection in goldfish (Cyprinus carpio) and to know the optimallevels of salt in the control of infection of Argulus sp. on goldfish. This study used aRandomized Complete Design (RAL), namely 3 and 1 control treatment with eachtreatment was repeated as many as 3 times, with a dose of the treatment 3 ppt, 6 ppt, 9ppt. Data analyzed with ANOVA. The results showed that the giving of the salt effecton the value of the prevalence, intensity of infection of Argulus sp. and survival rate ofgoldfish. The concentration of salt in controlling attacks Argulus sp. found in thetreatment of the G3 (9 ppt) that is the value of the prevalence of 60,17%, the value ofthe intensity of 1,54 ind/tail with survival rates of fish 93,33%.Key words : Cyprinus carpio, Argulus sp., salt (NaCl), prevalence, intensity